Analisis Efektivitas Implementasi Antara Kurikulum 2013 dan Kurikulum Merdeka di Sekolah Dasar - Erida Fitriani; Iqnatia Alfiansyah (SAP (Susunan Artikel Pendidikan), 2023)
The purposes of this research are to determine the differences in implementation of the 2013 Curriculum and the Merdeka Curriculum, obstacles to curriculum implementation, and the effectiveness of the 2013 Curriculum and the Independent Curriculum on learning in primary schools. This research used descriptive qualitative methods, the research subjects were the principal, grade 4 and 5 teachers and grade 4 and 5 students of UPT SD Negeri 29 Gresik. Data collection instruments used in-depth interviews and observation. The data in this research was in the form of sentences which will be analysed in depth. Research data collection was carried out in June 2023. Research procedures were carried out in stages, namely (1) the planning stage including a survey of curriculum use on research subjects, (2) the preparation stage by preparing the instruments that will be used to collect data and preparing data sources, (3) implementation stage and (4) reporting stage. The results of the research demonstrates that the implementation of the 2013 Curriculum is not optimal, because several obstacles have not been resolved, while the Independent Curriculum has the potential to provide a better learning experience and focuses on the characteristics of students.